PENGEMBANGAN MEDIA KARTU BILANGAN BERBASIS MATH GAMES DENGAN PENDEKATAN PMRI PADA MATERI PENJUMLAHAN BERSUSUN KELAS II SD - Rino Wijayanti; Jayanti; Ida Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop valid and practical math games-based number card media with the PMRI approach on compound addition material for grade II of SD Negeri Ringin Agung. This study uses the R&D method found in the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The instruments in this study used questionnaires and documentation. The questionnaire was presented to validators of material, media, language, teachers and students while the results of one to one were 4 students and small groups of 15 students of grade II of SD Negeri Ringin Agung. The results of validation by material experts on number card media based on math games obtained a score with a percentage of 94%, including the